2023
DOI: 10.1039/d2tc04902c
|View full text |Cite
|
Sign up to set email alerts
|

Tunable and enhanced mechanoluminescence in LiYGeO4:Tb3+via Bi3+ → Tb3+ energy transfer

Abstract: Mechanoluminescence (ML) materials, which can emit light under external mechanical stimuli, have attracted wide attention in diverse applications such as display, anti-counterfeiting and 3D signature. However, weak ML intensity and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Mechanoluminescence (ML) is the mechanical-photon conversion process of a material under mechanical stimuli such as impact, torsion, stretching, and friction. [1][2][3][4][5][6] In 1605, Bacon first observed the ML phenomenon by scraping sugar. [7] In 1966, Butler discovered the deformation luminescence phenomenon of alkali metal halides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanoluminescence (ML) is the mechanical-photon conversion process of a material under mechanical stimuli such as impact, torsion, stretching, and friction. [1][2][3][4][5][6] In 1605, Bacon first observed the ML phenomenon by scraping sugar. [7] In 1966, Butler discovered the deformation luminescence phenomenon of alkali metal halides.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32][33][34] By adjusting the host composition and crystal structure, changing the dopant ions and content, activating ion coexistence and growing heterojunctions, improved ML intensity, sensitivity and reduced ML threshold, and full coverage of ML spectrum of ultraviolet-visible-infrared (UV-Vis-IR) light have been realized. [2,29,[35][36][37][38] In short, the research ideas of ML materials are divided into two parts. First, doping luminescent centers in piezoelectric materials and creating suitable defects (e.g.,: Ca 4 Nb 2 O 9 :Pr 3+ , [39] LiNbO 3 :Nd 3+ [40] ) to achieve ML.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Shao et al proposed a way to enhance the ML intensity of Tb 3+ by Bi 3+ →Tb 3+ energy transfer in LiYGeO 4 toward multicolor ML emission. [6] Tu et al reported that (Ca 1-x Sr x ) 8 Mg 3 Al 2 Si 7 O 28 : Eu 2+ can achieve multicolor ML from green to blue by adjusting the Sr 2+ content. [7] However, ion codoping or lattice engineering tuning are too difficult to precisely control in practical applications to achieve the desired emissions.…”
Section: Introductionmentioning
confidence: 99%
“…proposed a way to enhance the ML intensity of Tb 3+ by Bi 3+ →Tb 3+ energy transfer in LiYGeO 4 toward multicolor ML emission. [ 6 ] Tu et al. reported that (Ca 1‐ x Sr x ) 8 Mg 3 Al 2 Si 7 O 28 : Eu 2+ can achieve multicolor ML from green to blue by adjusting the Sr 2+ content.…”
Section: Introductionmentioning
confidence: 99%